Analysis of Environmental Initiatives on Business Performance Sustainability at the Lake Naivasha Ecosystem, Kenya - Oribu, William Sagini; Agwata, Jones F.; George, Gongera Enock (My University, 2014)
Increasing degradation of the natural environment is one of the main threats to human survival in the long term. Business enterprises’ environmental commitment has, therefore, become an important variable in most of today’s competitive business environment. Activities of most enterprises are the main causes of environmental degradation which in turn impact on their performance. This study therefore looks at the specific business environmental initiatives and how they impact on their performance. The overall objective of the study was to establish the impact of environmental initiatives on business performance sustainability around Lake Naivasha. In order to achieve this objective, the research was guided by various specific objectives which included examining forms of environmental degradation, examining environmental initiatives put in place to mitigate on degradation, and examining effects of environmental initiatives of various business operations on social capital. Both primary and secondary data were collected for the purposes of the study. Primary data was collected through various instruments including questionnaires administered to individual respondents, focus group discussions, in depth interviews and observation schedules. Secondary data was obtained from previous study reports, articles, professional journals, various businesses’ monitoring records, annual sales reports and any other relevant literature that the researcher came across in the course of the study. The collected data was interpreted and analysed using discriminant analysis. The Scientific Package for Social Studies (SPSS) was used for the analysis. The study design was descriptive survey in order to pick behaviours which needed to be mitigated for purposes of enterprise performance sustainability. Purposive random sampling was used from the target population which comprised of farming, hospitality and fishing sectors. For purposes of establishing the views of the stakeholders, the officials of various organisations that have interests on the Lake Naivasha ecosystem were incorporated into a focus group and their views were sought through group discussions. The key findings of the study were that; the main forms of environmental degradation are nutrients discharge to the lake, water abstraction, cutting of trees, overgrazing and green house gases effects. The implication of the findings is that unless businesses concerned address environmental issues their performance sustainability may not be assured going forward. The study recommends that an evaluative criteria defining the impacts that are acceptable to the society be determined, policy bundles that are currently in place be reviewed to achieve diverse societal objectives, strategic decisions made by organisations operating in the area be assessed in light of the actors involved and investment in better information monitoring and enforcement of rules and regulations be undertaken. Lastly, since specific organisational sustainability outcomes seem to consistently fail to meet broad societal expectation, the articulation of stakeholder interests need to be considered by involving all actors in the environmental governance process.
Keywords: Environmental initiative on Business Performance Sustainability; Lake Naivasha; Kenya